About the Crusaders School, its Domicile and their main Artefact - Duňa SLAVÍKOVÁ (Sztuka i Dokumentacja)
The text examines the complex activities of a group of Czech artists, active mostly in the sixties and seventies, named after a pub where they met and drank beer, their ideological drink and artefact. In opposition to the cultural policies of Czech totalitarian structures, their artistic production introduced new practices that combined existing media from visual art, poetry, film, happening and music, abandoning the traditional terms of style, medium and representation. Their political consciousness and civil disobedience in conjunction with a playful state of mind in reaction to the times, the encouragement of humour and play in artistic creation generated a cultural environment that resulted in persecution in the past and in an inadequate acknowledgement today.